GaLactic and Extragalactic All-sky Murchison Widefield Array survey eXtended (GLEAM-X) I: Survey description and initial data release. (23rd August 2022) - Hurley-Walker, N.; Galvin, T. J.; Duchesne, S. W.; Zhang, X.; Morgan, J.; Hancock, P. J.; An, T.; Franzen, T. M. O.; Heald, G.; Ross, K.; Vernstrom, T.; Anderson, G. E.; et al.
Abstract: We describe a new low-frequency wideband radio survey of the southern sky. Observations covering 72–231 MHz and Declinations south of +30^° have been performed with the Murchison Widefield Array "extended" Phase II configuration over 2018–2020 and will be processed to form data products including continuum and polarisation images and mosaics, multi-frequency catalogues, transient search data, and ionospheric measurements. From a pilot field described in this work, we publish an initial data release covering 1, 447 deg^2 over 4 h≤ RA≤ 13 h, -32.7^° ≤ Dec ≤ -20.7^° . We process twenty frequency bands sampling 72–231 MHz, with a resolution of 2′–45 ′′, and produce a wideband source-finding image across 170–231 MHz with a root mean square noise of 1.27±0.15 mJy beam^-1 . Source-finding yields 78, 967 components, of which 71, 320 are fitted spectrally. The catalogue has a completeness of 98% at 50 mJy, and a reliability of 98.2% at 5σ rising to 99.7% at 7σ . A catalogue is available from Vizier; images are made available via the PASA datastore, AAO Data Central, and SkyView. This is the first in a series of data releases from the GLEAM-X survey.